EASE OF DOING BUSINESS IN INDONESIA: A LONG ROAD - Tomi Setianto (Universitas Ahmad Dahlan, 2020)
This paper discusses the ranking of Indonesia in various indicators of measuring Ease of doing business and attempts that Indonesia has taken to move up the Ease of doing business ranking. Indonesia's rank in the World Banks Ease of Doing Business 2020 report stuck at 73 from last year ranking. Since the last two years, Indonesia did not have any significant policy in improving the business climate despite many measures already been taken by the government. The lack of a policy to improve the business climate and the increasing difficulty in starting a business has led to Indonesia's EODB ranking stagnation. Indonesia needs to reform more in order to be in top 50's EODB ranking by improving its business environment especially around starting a business, enforcing contracts, trading across border and registering property.